Perjuangan Perempuan Single Parent di Nagari Lubuk Malako: Menyiasati Tantangan dalam Penghidupan Keluarga - Oktarina, Solastri; Akbar, Waza Karia; Wijaya, Wibi; Harisnawati, Harisnawati; Rahayu, Sri (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
In Nagari Lubuk Malako, Sangir Jujuan District, South Solok Regency, pre-prosperous single-parent women face unique challenges due to divorce, widowhood, or separation. These women undertake all household responsibilities, balancing roles as both the head of the household and homemaker to ensure their families' needs are met and their children lead fulfilling lives despite the absence of a father figure. This study aims to investigate the roles of these women in the specified region. Using a qualitatif research methodology, data were collected through in-depth interviews and participan observation. The findings indicate that these women perform multiple critical roles: 1) breadwinner, 2) housewife, 3) child moral educator, and 4) head of the family. This research highlights the significant contributions and resilience of single-parent women in maintaining their households and supporting their children's well-being.